Strategy to Improve the Quality of Online Seaman Book Services at the Harbor Master and Port Authority (KSOP) Class II of Benoa - Sriningrum, Kadek Dwi; Amrullah, Romanda Annas; Agustina, Eka Nurmala Sari; Sianturi, Intan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Seaman Book Online is an online service system that makes it easier for Seamans to take care of seaman books, official documents that record Seamans' identities and work experiences without having to come directly to the office. This research uses a qualitative descriptive approach through observation, interviews, and documentation. The results show that service quality is influenced by six management elements: man, money, materials, machines, methods, and markets. The obstacles faced include a shortage of employees, limited equipment, network disruptions, and SOPs that are not fully effective. The improvement strategy is carried out through human resource arrangements, equipment procurement, facility optimization, and socialization of online services, including through social media. The Online Seaman Book service at Harbor Master and Port Authority (KSOP) Class II of Benoa has been running well, with a Community Satisfaction Index (IKM) value of 3.93 in the "Very Good" category.